Mycobacteriophage Yasnaya_Polyana and its engineered lytic derivative: specificity of regulatory motifs and lytic potential - Shitikov, Egor; Malakhova, Maja; Kuznetsova, Sofya; Bespiatykh, Dmitry; Gorodnichev, Roman; Kiselev, Sergei; Kornienko, Maria; Klimina, Ksenia; Strokach, Aleksandra; German, Arina; Lebedeva, Anastasiia; Fursov, Mikhail; et al. (Frontiers in Microbiology, 2025)
IntroductionThe growing prevalence of multidrug-resistant Mycobacterium tuberculosis and nontuberculous mycobacteria (NTM) highlights the urgent need for alternative therapeutic approaches. Mycobacteriophages, viruses that selectively infect mycobacteria, have emerged as promising tools. Here, we report the isolation and characterization of a new subcluster K4 phage, Yasnaya_Polyana, with a focus on its regulatory motifs and engineered lytic variant.MethodsThe phage was isolated by enrichment on Mycobacterium smegmatis mc(2)155, followed by genome sequencing and functional annotation. Start-Associated Sequences (SAS) and Extended SAS (ESAS) were analyzed in silico across 188 cluster K phages. A lytic derivative, YPΔ47, was engineered by deleting the repressor gene and characterized in terms of morphology, stability, infection dynamics, and host range.ResultsYasnaya_Polyana exhibited siphovirus morphology and high genetic similarity with other subcluster K4 phages. Regulatory motif analysis revealed a reduced abundance of SAS and ESAS elements in subcluster K4 phages, including Yasnaya_Polyana, along with specific ESAS sequence deviations. The engineered YPΔ47 mutant retained morphology and infection parameters comparable to the wild-type phage but exhibited a decline in lysogeny frequency (from 18% to <0.01%), confirming a lytic phenotype. Host range analysis revealed limited activity of YPΔ47 against NTM, while the phage demonstrated a high efficiency of plating (EOP = 10−1) on M. tuberculosis H37Rv and effectively lysed clinical isolates.DiscussionThese findings suggest that Yasnaya Polyana, and apparently other subcluster K4 phages, harbor distinct regulatory features that may reflect divergent transcriptional control strategies. Moreover, YPΔ47 shows potential as a candidate for phage therapy targeting mycobacterial infections.